Combined effects of х-ray and γ - radiation on cell human peripheral blood in vivo and in vitro (Experimental biology, 2016)
The results of the study in vivo effects of chronic influence of X-rays on rentgenlaboratory medical workers, as well as assessed the radiosensitivity and the ability of peripheral blood lymphocytes in the formation of an adaptive response by the action of γ-radiation. Conducted in vitro experiments to study the combined effects of X- and γ- radiation on cells of peripheral blood from healthy donors. Studied the frequency and spectrum of chromosome aberrations have 10 people working in the medical X-ray laboratory in age from 25 to 59 years of work experience from 4 to 31 years. The control group consisted of two subgroups - p. Tausugur residents of Almaty region (41 people) and Almaty (15 people), who had no professional contact with sources of ionizing radiation. Experiments on the radiosensitivity and adaptive response induction were conducted on 10 people from each sample. There was a significant increase in the frequency of chromosome aberrations as a chromosome and chromatid type in the surveyed group of radiologists compared to the control, indicating that the mutagenic effect of factors of professional environment. Correlations between age, duration of work in harmful conditions, and yield of chromosomal abnormalities have been identified. Further exposure to 2 Gy γ-radiation detected high radiation sensitivity of peripheral blood lymphocytes and induction of radiologists multiaberrant large number of cells.  For some individuals, they accounted for 30% of the number of cells containing chromosomal abnormalities. Induction of adaptive response reaction scheme 0.05 / 2 Gy with intervals of 4 hours at G0 phase of the cell cycle revealed heterogeneity of the studied group on this indicator - in seven radiologists formed a pronounced adaptive response, in 1 there is a lack of this reaction, the two - radiosensibilization . Conducting in vitro experiments with fractional (at 0,033 Gy) exposure in adapting doses blood of healthy donors with X-rays at the medical setting, and then irradiating the same blood after 4 h. Damaging dose of 2 Gy γ-radiation shows that the adaptive response is only formed with a single adapting the irradiation dose. Repeated (fractional) accumulation irradiation adapting multiple doses of X-radiation, leads to an increase in the frequency of chromosome aberrations blood samples after irradiation damaging dose of 2 Gy (radiation-sensitizing effect), i.e. fractionated radiation exposure suppresses the protective function of the cells, in particular adaptive response, and there is a tendency to increase the frequency of aberrations per aberrant cell.
Keywords: chromosomal aberrations; radiosensitivity; adaptive re¬sponse; γ-radiation; x-rays.